Treating addicted survivors of trauma - Evans, Kathie (Guilford Press, 1995)
Philosophy of treatment Rachel's story The impact and process of abuse Addiction and survivors A model for dual recovery and crisis stage interventions Interventions in later stages of recovery Depression, anger, and dissociation The addicted adolescent survivor Addicted survivors in their families, at work, and in therapy groups Afterword: The dragon dies, the child survives